Zinc Oxide Nanoparticle Reinforced Waste Buffing Dust Based Composite Insole and Its Antimicrobial Activity - Thuhin K. Dey; Arman Hossain; Mamun Jamal; Rama K. Layek; Md. Elias Uddin (Advances in Polymer Technology)
The objective of this research is to use zinc oxide nanoparticles (ZnONPs) combined with buffing dust to develop footwear insole with antibacterial properties. In addition, performance analysis (mechanical, chemical, and thermal) of fabricated insole is also the integral consideration of this study. With such aim, antimicrobial composite insoles were fabricated via simple solution mixing of ZnONPs and natural rubber latex (NRL) binder along with buffing dusts with optimum ratio. Then, removal of water was considered by mechanical pressing followed by natural drying in sunlight. The chemical bonding and material interactions of composites were investigated using FT-IR and XRD, respectively. TGA analysis confirmed the thermal stability of composites, while SEM and OTR are elucidating the surface morphology and gas barrier properties, respectively. Tensile strength, elongation, flexibility, hardness, and water absorption of prepared composite with optimum NRL content were increased by 39, 31, 30, 38, and 28%, respectively. Finally, 78% antimicrobial performance was achieved against the suspension of (1.5×106 CFU/mL) bacterial strain Staphylococcus aureus.